SENSITIVITAS PENDAPATAN ATAS BUNGA PENJAMINAN SIMPANAN TERHADAP RISIKO ASSET TRANSMUTATION PADA KEPAILITAN BPR DI INDONESIA - Hesti Budiwati (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2021)
To uncover the impact or contribution of LPS to rural bank’s bankruptcy conditions in Indonesia, then the objective of this research aims to know the effect of deposit insurance interest on asset transmutation risk on rural banks in Indonesia. The analysis method used is path analysis and sobel test. As an independent variable is the sensitivity of deposit insurance interest and the dependent variable is deposit and loan, while the mediation variable is interest cost. The researched data are quarterly financial statement for 4 quarters before the rural banks bankrupt and by comparison also an analysis on quarterly financial statement for 4 quarters on non-bankrupt rural banks. The purposive sampling method obtain sample consist of 144 quarterly financial statements of 36 bankrupt banks and 144 quarterly financial statements of 36 non-bankrupt banks from 2006 to 2018. The results of the study showed that the sensitivity of deposit insurance interest affect significanly on asset transmutation risk. However, there is a difference in the direction of the effect of deposit insurance interest on asset transmutation risk which is on bankrupt rural banks affect significanly in negative direction, while non-bankrupt rural banks affect significanly in positive direction. The results of sobel test also showed that the interest cost affect significanly as mediator between deposit insurance interest and the deposit and loan on bankrupt rural banks or non-bankrupt rural banks. The interesting result can be concluded from this study there is difference of rural banks asset transmutation risk in interest fluctuation between bankrupt and non-bankrupt rural banks.